KONTRIBUSI PELAKSANAAN FUNGSI KEPEMIMPINAN KEPALA MADRASAH DAN IKLIM ORGANISASI TERHADAP KINERJA GURU MTSN DI KABUPATEN SOLOK - Livia Susanti (al-fikrah: Jurnal Manajemen Pendidikan, 2016)
This Thesis discusses the contribution of the implementation of leadership function of the Madrasah organization atmosphere toward work performance of MTsN teachers in Solok. The research is categorized as expost facto by using quantitative with correlational research as its approach. This research took all the teachers of the MTsN in Solok as the samples. In totalthere were193 persons and 78 of them were selected as the research samples by means of stratified proportional random sampling technic. The collected data used questionaire instrument by using Likert scale. The first and second hypothesis were tested by using correlation technique and simple regression. Meanwhile, the third hypothesis was tested by using double regression.The result of the data analysis concludes that : (1) The implementation of the leadership function of the Madrasah Headmaster contributes significantly 46.8% towards work performance of the teachers of the MTsN in Solok, (2) organization atmosphere contributes significantly 57.7% towards work performance of the teachers of the MTsN in Solok, (3) the implementation of the leadership function of the Madrasah Headmaster and organization atmosphere contribute significantly 63.3% to the work performance of the MTsN teachers in Solok.Key Words: Implementasi, fungsi kepemimpinan, iklim Organisasi, kinerja guru